Optimization on the Credit Risk of Companies in Malaysia With Data Envelopment Analysis Model - X. Agnes Lai, J.; H. Lam, j.; S. Lam, W. (International Journal of Engineering and Technology, 2018)
Financial institutions provide financial services to their clients or retail customers where money is managed. Credit risk has been identified as one of the dominant risks that affect the performance of a company. A firmâ€™s efficiency with different credit risk management practices is still unknown. This research aims to evaluate the credit risk management and efficiency of the financial institutions that are publicly listed in Bursa Malaysia from year 2013-2016 with the Data Envelopment Analysis (DEA) model. Based on the financial ratios, the DEA model allows the relative efficiency of a set of companies to be assessed by solving a linear programming model. The results show that ALLIANZ, APEX, BURSA, ECM, LPI and TAKAFUL are efficient in terms of their credit risk management. This study identifies the efficient and inefficient financial companies in Malaysia.Â Â